Preparation and Evaluation of Metronidazole Benzoate Periodontal Patches - Tasneem, Farhana; Alam, Marzia; Pathan, Md Saiful Islam (Bangladesh Pharmaceutical Journal, 2015)
Periodontitis is a serious gum disease that damages the soft tissue and destroys the bone that supports the teeth. According to WHO, globally 1520% of middle-aged (35-44 years) adults, suffer from severe periodontal (gum) diseases. Metronidazole benzoate is an antibacterial agent prescribed against different diseases including, periodontitis and several other protozoal infestations. The aim of this experiment was to formulate intrapocket periodontal patches of metronidazole benzoate to provide site specific therapeutic activity with very small loading dose. Nine (F1 to F9) formulations of metronidazole benzoate were prepared by solvent casting method using ethyl cellulose and Eudragit RLPO as polymers, dibutyl phthalate as plasticizer and alcohol and chloroform as solvent system. Various physicochemical evaluations including FTIR, Trinocular Microscopic images, folding endurance, surface pH and content uniformity were determined. All the batches revealed content uniformity between 94.0% to 98.0%. It was observed that the thickness and weight of the films were directly proportional to the total solid content of the film. F1 showed the lowest thickness and weight (232.5 ?m and 35.45 mg respectively) and F9 displayed the highest (864.7 ?m and 85.23 mg respectively). Folding endurance was directly proportional to the content of plasticizer. Formulation F3 was considered as the best formulation based on its transparent appearance, folding endurance (>200 times), surface pH (6-7) and 97.5% content uniformity. Bangladesh Pharmaceutical Journal 18(2): 97-102, 2015